The Heuristic Power of Theory Classification, the Case of General Relativity (Culturas Científicas, 2026)
In this article, we explore the heuristic power of the theoretical distinction between structural and mechanistic theories applied to the case of General Relativity. According to the distinction, theories and theoretical elements can be classified into two different groups, each with clear ontological, epistemic and functional content. Being so, to identify the group to which a theory belongs would suffice to know a priori its prospects and limitations in these areas without going into a detailed technical analysis. We make the exercise here with General Relativity, anticipate its ontological, epistemic and functional content and show afterwords that such expectations are justified in this case, being consistent with formal issues of General Relativity. With this, we attempt to make a case for the use of the distinction as a powerful tool for scientific and philosophical analysis.
Keywords: Framework theories; Interaction theories; General Relativity; Quantum Gravity; Theory Classification